Feeding dietary inclusion of inulin on immune status, protein metabolism, and growth performance of Kedu chicken - Suthama, N.; Mangisah, I.; Krismiyanto, L.; Yunianto, V. D.; Mulyono, M. (Diponegoro University, 2025)
Indonesian Indigenous poultry originated from the central part of Java Island, called Kedu chick-en, given diet added with inulin of dahlia tuber extract (IDTE) to evaluate body resistance and protein deposition. The experimental animals were 150 birds of 14-day-old Kedu chicken (initial body weight was 148 ± 16.4 g) until 12 weeks old. Dietary treatments were T1: farmer’s diet with protein concen-trate; T2: T1 + 1.2% inulin of IDTE, and T3: modified diet with common protein sources + 1.2% IDTE. A completely randomized design was assigned with 3 treatments (5 replications with 10 birds each). Parameters observed were rate of passage, protein and fiber digestibilites, Nitrogen (N) and Cal-cium (Ca) retentions, body resistance (plasma concentration of corticosterone/CTC, level of immuno-globulin A/IgA, and heterophyl-lymphocyte/H/L ratio), protein metabolism (fecal Nτ–methylhistidine/Nτ–MH and muscle protein mass), feeds consumption, feed conversion ratio (FCR), and body weight gain (BWG). Analysis of variance and Duncan’s test were applied to analyze data. Rate of passage, N and Ca retentions, BWG, IgA level, and muscle protein mass increased; in contrast, FCR, fecal Nτ–MH, and plasma CTC decreased due to the feeding effect of the T3 diet. All parameters, except IgA level, between treatment T1 and T2 indicated similar values. It can be concluded that a modified diet added with IDTE (T3) can modulate the increase in N retention and immune status, with the decrease in muscle protein degradation indicated by low fecal Nτ–MH excretion, and finally, brings about a bet-ter growth rate, with higher muscle protein deposition.